Bcgitis and Vaccine-Derived Poliovirus Infection in a Patient with a Novel Deletion in RAG1 Binding Site. (April 2013) - Canessa, C.; Romano, F.; Lippi, F.; Bianchi, L.; Kashef, S.; Rezaei, N.; Moriondo, M.; Nieddu, F.; Martini, M.; Azzari, C.
A girl who developed severe BCGitis and vaccine-derived poliovirus infection was discovered to have a novel deletion of RAG1. A neonatal screening program for SCID would identify affected infants at birth, before live vaccines are administered.